2010
DOI: 10.1002/lsm.20882
|View full text |Cite
|
Sign up to set email alerts
|

Histological comparison of two different fractional photothermolysis devices operating at 1,550 nm

Abstract: We have characterized the lesion depth and width for the for two different Fractional Photothermolysis devices (SR750 vs. SR1500). The device with the adjustable spot size (SR1500 or Fraxel re:store) provides generally deeper lesions at the same energy level. It remains to be shown whether increased lesion depth improves efficacy for certain clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 22 publications
1
36
0
Order By: Relevance
“…Such studies mainly involve exposing the excised skin samples to lasers in order to evaluate the histological changes that occur immediately after laser treatment, thereby not requiring organotypic culturing of skin samples. 12,13 The histological changes following laser exposure, as assessed by ex vivo methods, have been found to be nearly the same as those obtained in in vivo tests. Exposure of a skin sample to carbon dioxide fractional laser ex vivo has revealed many microscopic treatment zones and thermal coagulation zones where the epidermis and the dermis were histologically ablated.…”
Section: Advantages Of Using Skin Explants In Laser Studiessupporting
confidence: 54%
“…Such studies mainly involve exposing the excised skin samples to lasers in order to evaluate the histological changes that occur immediately after laser treatment, thereby not requiring organotypic culturing of skin samples. 12,13 The histological changes following laser exposure, as assessed by ex vivo methods, have been found to be nearly the same as those obtained in in vivo tests. Exposure of a skin sample to carbon dioxide fractional laser ex vivo has revealed many microscopic treatment zones and thermal coagulation zones where the epidermis and the dermis were histologically ablated.…”
Section: Advantages Of Using Skin Explants In Laser Studiessupporting
confidence: 54%
“…[65] It has been shown that the use of higher energy settings and multiple laser passes leads to improved clinical results, while use of increased densities results in increased post-treatment erythema, edema, and hyperpigmentation. [66] Similar to NAFLs, AFLs work by achieving collagen contraction and neocollagenesis. Split-face studies have found equal or slightly greater clinical improvement scores with the AFL than with the NAFL, only at the cost of higher chances of post procedural erythema and hyperpigmentation.…”
Section: Laser Therapy For Acne Scarsmentioning
confidence: 99%
“…The depth-width ratio (DWR) for most fractional lasers is about 4–5. [6] The higher the DWR, more the dermal volume that can be thermally damaged. As the width of most fractional lasers is almost the same due to the intrinsic quality of the fractional ‘technology’, the depth is the variable factor that may play a predominant role in fractional laser efficacy.…”
Section: Acne Scar Topography and Fractional Lasersmentioning
confidence: 99%
“…Another issue is that the substrates used in studies are ex vivo models[12468–18] and their replicability on facial skin is doubtful [Figure 2]. Extrapolating data from studies done for rhytides[2527] are not useful as the dose and depth required are less as compared to acne scars.…”
Section: Invasive (Histological) Assessment Of Fractional Lasermentioning
confidence: 99%
See 1 more Smart Citation